Transferring expert system technology to potential users: A case study of Alvey's awareness clubs. (4th August 2014) - Ray, Tim
The processes by which the United Kingdom's government–sponsored Alvey Programme for supporting advanced information technology has used research clubs to promote user awareness of expert systems are examined. It is explained how these clubs provided a mechanism whereby would–be users of expert systems in nine different sectors of UK business could gain experience of the development and implementation of a medium–sized expert system, built by independent contractors, that was relevant to their interests. An attempt is made to evaluate the appropriateness of the research clubs as a device for generating knowledge about a relatively new technology (expert systems) and, at the same time, transferring that knowledge to communities of prospective users. It is argued that the clubs provided members with low–cost experience of the specification and use of expert systems, together with an ability to evaluate the constraints and opportunities associated with future progress in the technology. Contractors, for their part, derived experience of expert system construction and established links with possible customers. The factors that appeared to be instrumental in enabling the awareness club to achieve their objectives are analysed.